(untitled) (Research, Society and Development, 2021)
Aim: To describe the main acupuncture points used in the treatment of primary dysmenorrhea. Method: This is a review of narrative literature, where clinical trials were used, with the following descriptors: “Acupuncture”, “Acupuncture Points”, “Chinese Medicine” e “Primary Dysmenorrhea”. The searches took place in the SciELO, PubMed, LILACS, PEDro, CAPES Journal Portal, ScienceDirect and Cochrane databases, in the period from 2011 to 2021, with articles selected between January 2016 to December 2021, in any language, that presented in their research objective to describe the main acupuncture points used in the treatment of primary dysmenorrhea. Duplicate and paid review articles were considered unskillful, meta-analyses and women with associated pathologies. Results: 334 articles were identified, of which 5 met the inclusion criteria, covering a total of 348 patients diagnosed with primary dysmenorrhea. The therapeutic use of spleen 6 (BP-6) was evaluated in three of the five selected publications, meeting several objectives. The most evaluated primary outcome was the intensity of menstrual pain. Conclusion: It is concluded that acupuncture can be used as an effective and safe method to treat women with primary dysmenorrhea.